Perkawinan Orang Aceh dengan Orang Bugis-Makassar : Studi Sejarah Empat Keluarga di Kota Makassar (1990-2004) - Amelia Putri J; Imam Puja Rabbani; Amirullah Amirullah (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This research examines inter-ethnic marriages between Acehnese and Bugis-Makassar communities in Makassar City from 1990 to 2004, which emerged as a consequence of social mobility, cross-cultural interaction, and compatibility of religious values. The purpose of this study is to explain the factors that trigger inter-ethnic marriages, the underlying customary processes, and the socio-cultural dynamics that occur within family life. This research uses historical methods, including the heuristic stage, source criticism, interpretation, and historiography, with data obtained thru in-depth interviews with four families and related documentary sources. The research findings indicate that holding a wedding requires cultural negotiation between the two groups, with some families adopting traditional Acehnese ceremonial customs, while others implement Bugis-Makassar traditions. In family life, couples face differences in values regarding communication, gender role division, and religious practices, which are then overcome thru a dialogue-based process of adaptation and compromise. This process results in the formation of hybrid cultural identities, the expansion of social networks, and the strengthening of inter-ethnic integration. Overall, intertribal marriages serve as a medium for cultural reconciliation and a means of building more inclusive social relationships in a multicultural society.